Study on Climate Change in Southwestern China - Li, Zongxing (Springer, 2015)
This thesis confirms many changes, including sharp temperature rise, interannual variability of precipitation, extreme climate events and significant decreases of sunshine duration and wind speed in southwestern China, and systemically explores the action mechanism between large-scale atmospheric circulation systems, the complicated topography, human activities and regional climate changes. This study also analyzes the response of glaciers to climate change so that on the one hand it clearly reflects the relationship between glacier morphologic changes and climate change; on the other, it reveals the mechanism of action of climate warming as a balance between energy and matter. The achievements of this study reflect a significant contribution to the body of research on the response of climate in cold regions, glaciers and human activities to a global change against the background of the typical monsoon climate, and have provided scientific basis for predictions, countermeasures against disasters from extreme weather, utilization of water and the establishment of counterplans to slow and adapt to climate change.